2010
DOI: 10.1063/1.3502681
|View full text |Cite
|
Sign up to set email alerts
|

Chain contraction and nonlinear stress damping in primitive chain network simulations

Abstract: Doi and Edwards (DE) proposed that the relaxation of entangled linear polymers under large deformation occurs in two steps: the fast chain contraction (via the longitudinal Rouse mode of the chain backbone) and the slow orientational relaxation (due to reptation). The DE model assumes these relaxation processes to be independent and decoupled. However, this decoupling is invalid for a generalized convective constraint release (CCR) mechanism that releases the entanglement on every occasion of the contraction o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 25 publications
4
21
0
Order By: Relevance
“…23) Figure 5 shows the damping function h( g) evaluated from the simulated G(t, g ). For well entangled chains, previous studies 13, 14,19) indicated that h( g ) obtained from the PCN simulations is insensitive to <Z> eq (which is in harmony with the experimentally observed type-A behavior). 4) This h( g ) for the well entangled chains is close to the prediction of the three-chain model 24) shown in Fig.…”
Section: Nonlinear Viscoelasiticity In Stress Relaxationsupporting
confidence: 79%
See 2 more Smart Citations
“…23) Figure 5 shows the damping function h( g) evaluated from the simulated G(t, g ). For well entangled chains, previous studies 13, 14,19) indicated that h( g ) obtained from the PCN simulations is insensitive to <Z> eq (which is in harmony with the experimentally observed type-A behavior). 4) This h( g ) for the well entangled chains is close to the prediction of the three-chain model 24) shown in Fig.…”
Section: Nonlinear Viscoelasiticity In Stress Relaxationsupporting
confidence: 79%
“…2 Figure 3 shows the nonlinear relaxation modulus G(t, g) simulated for representative <Z> eq values. G(t, g) for <Z> eq = 9.2 exhibits strong damping for large g, which is similar to the behavior of G(t, g) simulated for well-entangled chains with <Z> eq = 23 and 30 (that agreed with the G(t, g) data for a PS melt 14) and a PS solution 19) , respectively). On the other hand, G(t, g) for <Z> eq = 4.7 exhibits rather weak damping.…”
Section: Model and Simulationssupporting
confidence: 79%
See 1 more Smart Citation
“…The PCN simulations have been performed for several systems such as linear polymers [34,[37][38][39], symmetric and asymmetric stars [38,40], comb branch polymer [41], polymer blends [38], and copolymers [42], and it has been showed that the PCN simulations can reproduce various rheological properties reasonably. Moreover, even under large and fast deformations [43][44][45][46][47][48][49] the PCN simulations show reasonable consistency with experiments. To locate the PCN model between multi-chain and single chain models, we have reported a comparison with single chain models on bidisperse blends [50] and a comparison with molecular simulations on the network statistics [51].…”
Section: Introductionmentioning
confidence: 81%
“…The simulation method has been shown capa-nonlinear viscoelastic properties of entangled polymers [17][18][19][20] .…”
Section: Introductionmentioning
confidence: 99%